The regeneration of Kuching downtown and the impacts of urban tourism - Chiong, Sik Ing. (Universiti Malaysia Sarawak (UNIMAS), 2008)
This research aims to study the downtown regeneration progress in relation to the local urban context. As the issues of flaw planning and regeneration program that do not fit congenially to their local contexts would cause the failures in the end, it is important to determine the factors that succeed the urban or downtown renewal program. The objectives of the study are i) to determine the perceptions of local communities and foreign visitors about Kuching downtown regeneration progress, and ii) to study the impacts of urban regeneration. In the efforts to implement significant and sustainable renewal projects, the three main aspects-economic, physical environment and socio-culture of the local context need to be well-studied and well-planned.